Identifikasi Glukosa Urin dan Keton Urin pada Pasien Tuberkulosis Paru yang Mendapat Terapi Obat Anti Tuberkulosis (OAT) Di Puskesmas Tlogosari Wetan - Hafidsya, Pradiana Syahwa; Kahar, Fitriani (Jaringan Laboratorium Medis, 2024)
Tuberculosis is a contagious infection caused by Mycobacterium tuberculosis. Anti-Tuberculosis Drug Therapy (OAT) given also has side effects, one of which is nephrotoxic. Laboratory examination of urine glucose identification can indicate if there is damage to the kidney glomerulus in the filtration process. The purpose of this study was to identify urine glucose and urine ketones in non-DM pulmonary TB patients with OAT treatment at the Tlogosari Wetan Health Center. This type of research is descriptive observational with a cross-sectional approach. The population was all TB patients who underwent examination at the Tlogosari Wetan Health Center. The research sample was a random urine sample from non-DM pulmonary TB patients. The examination method used was a dipstick using a reagent strip test. The results showed that out of a total of 30 non-DM pulmonary TB patients with OAT therapy (100%). A total of 6 (20%) patients were identified with urine glucose, with details of  intensive phase treatment 2 (7%) patients with trace urine glucose (±), while in the continuation phase 2 (7%) patients were identified with trace urine glucose (±) and 2 (7%) patients with low urine glucose (+1). The majority of positive urine glucose results were experienced by males with an elderly age range (46-65 years) of 4 patients (14%). The results of urine ketone identification showed that 2 (6.6%) patients were identified with urine ketones, namely trace (±) in intensive phase treatment, while 15 patients in the continuation phase had all negative urine ketones. The majority of positive urine ketone results were experienced by males with an adult age range (26-45 years) of 2 patients (14%). The conclusion of 30 non-DM pulmonary TB patients with OAT therapy who met the inclusion criteria, there were 6 (20%) patients identified with urine glucose and 2 (6.6%) patients identified with urine ketones. The impact of this study is expected for non-DM pulmonary TB patients to take OAT and have regular medical check-up.